Imperfect Predictors for Lung Cancer Immunotherapy—A Field for Further Research - Wojas-Krawczyk, Kamila; Kubiatowski, Tomasz (Frontiers in Oncology, 2020)
The armamentarium for lung cancer immunotherapy has been strengthened using two groups of monoclonal antibodies that block PD-1 or PD-L1 molecule. Anti-PD-1 antibodies, which include pembrolizumab and nivolumab, block the programmed death 1 receptor on the lymphocyte surface, resulting in an increase the activity of these cells. Anti-PD-L1 antibodies, including atezolizumab, durvalumab and avelumab, block the ligand for PD-1 molecule on tumor cells and on tumor-infiltrating immune cells. This type of interaction increases the activity of cytotoxic lymphocytes in the tumor environment, which become able to kill cancer cells. The effectiveness of both groups of antibodies has been proven in many clinical trials, which translated into positive immunotherapeutic registrations for cancer patients in the whole world. The expression of PD-L1 molecule on cancer cells is the only predictive factor validated in prospective clinical trials for qualification to immunotherapy in advanced non-small cell lung cancer (NSCLC) patients. However, it should be considered whether it is an ideal predictive factor. Unfortunately, in patients with PD-L1 expression on tumor cells the lack of immunotherapy response could be observed, and the effectiveness of this treatment method also may occur in patients without PD-L1 expression. Unfortunately, the mechanism of anti-tumor immune response is extremely complex, multi-stages, and depends on many factors. Cancer cells could be recognized by the immune system provided tumor-specific antigens presentation, which arise as a result of somatic mutations in tumor cells. It seems that high tumor mutation burden (TMB) may, in the future, become an important factor for qualification of NSCLC patients to immunotherapy. The intensity of lymphocytes infiltration in tumor tissue may be another predictive factor for immunotherapy. There are also reports on the effectiveness of immunotherapy using anti-PD-L1 antibodies in patients with high expression of genes associated with the effector function of T lymphocytes (i.e. their ability to produce IFN-gamma). This does not end of potential factors list that become useful in qualification of cancer patients to immunotherapy. There remains a need to search for new and perfect predictive factors for immunotherapy.